2013
DOI: 10.1124/dmd.112.050534
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Catalytic Function of Human Hydroxysteroid Sulfotransferase hSULT2A1 by Formation of Disulfide Bonds

Abstract: The human cytosolic sulfotransferase hSULT2A1 catalyzes the sulfation of a broad range of xenobiotics, as well as endogenous hydroxysteroids and bile acids. Reversible modulation of the catalytic activity of this enzyme could play important roles in its physiologic functions. Whereas other mammalian sulfotransferases are known to be reversibly altered by changes in their redox environment, this has not been previously shown for hSULT2A1. We have examined the hypothesis that the formation of disulfide bonds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…41 Indeed, our current results on the modification of hSULT2A1 with three PCB-quinones also showed consistent decreases in catalytic activity. There was, however, an increase in the catalytic activity at some concentrations of the non-chlorinated biphenyl quinone, PBQ.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…41 Indeed, our current results on the modification of hSULT2A1 with three PCB-quinones also showed consistent decreases in catalytic activity. There was, however, an increase in the catalytic activity at some concentrations of the non-chlorinated biphenyl quinone, PBQ.…”
Section: Discussionsupporting
confidence: 78%
“…41,55,57,6568 While most of these SULTs have been members of family 1, we have recently reported that the catalytic activity of human hydroxysteroid sulfotransferase hSULT2A1 is also sensitive to formation of disulfide bonds at key cysteine residues. 41 Alteration of the structure and function of hSULT2A1 through oxidative post-translational changes at cysteine residues led us to hypothesize that changes in catalytic function may also result from reaction of the enzyme with electrophiles that form adducts at those cysteine residues. Such adduct formation would likely alter sulfation with concomitant effects on the metabolism of xenobiotics as well as endogenous molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the reduction may be caused by PCB3 hydroquinone or semiquinone radicals, as described with benzoquinones (Williams 1963, Winterbourn 1981). Interestingly, after adduct formation with sulfhydryl groups in peptides/proteins like N-acetyl cysteine (Wangpradit et al 2009) and human hydroxysteroid sulfotransferase hSULT2A1 (Qin et al 2013b) only hydroquinone derivatives of PCBs were identified, while the adducts we found with cytochrome c were all quinoid derivatives of PCBs. This may be caused by the oxidation of a hydroquinone or semiquinone adduct by the ferric heme group in cytochrome c resulting in reduced cytochrome c and a PCB quinone adduct.…”
Section: Discussionmentioning
confidence: 87%
“…60,82 PCB quinones are also capable of protein adduct formation, a mechanism by which they can interfere with the physiological functions of a protein. [83][84][85] OHPCBs also represent substrates for conjugation reactions catalyzed by sulfotransferases (SULTs), UDP-glucuronosyl transferases (UGTs) or glutathione Stransferases (GSTs) to yield their respective sulfate, glucuronic acid or mercapturic acid conjugates. 73,86,87 These conjugation reactions increase the polarity of PCBs, which results in enhanced hydrophilicity and which is typically assumed to result in renal or biliary excretion.…”
Section: Figure 1-2mentioning
confidence: 99%